Orthogonally combined motion‐ and diffusion‐sensitized driven equilibrium (OC‐MDSDE) preparation for vessel signal suppression in 3D turbo spin echo imaging of peripheral nerves in the extremities - Cervantes, Barbara; Kirschke, Jan S.; Klupp, Elizabeth; Kooijman, Hendrik; Börnert, Peter; Haase, Axel; Rummeny, Ernst J.; Karampinos, Dimitrios C. (Magnetic resonance in medicine, 2018)
Purpose To design a preparation module for vessel signal suppression in MR neurography of the extremities, which causes minimal attenuation of nerve signal and is highly insensitive to eddy currents and motion. Methods The orthogonally combined motion‐ and diffusion‐sensitized driven equilibrium (OC‐MDSDE) preparation was proposed, based on the improved motion‐ and diffusion‐sensitized driven equilibrium methods (iMSDE and FC‐DSDE, respectively), with specific gradient design and orientation. OC‐MDSDE was desensitized against eddy currents using appropriately designed gradient prepulses. The motion sensitivity and vessel signal suppression capability of OC‐MDSDE and its components were assessed in vivo in the knee using 3D turbo spin echo (TSE). Nerve‐to‐vessel signal ratios were measured for iMSDE and OC‐MDSDE in 7 subjects. Results iMSDE was shown to be highly sensitive to motion with increasing flow sensitization. FC‐DSDE showed robustness against motion, but resulted in strong nerve signal loss with diffusion gradients oriented parallel to the nerve. OC‐MDSDE showed superior vessel suppression compared to iMSDE and FC‐DSDE and maintained high nerve signal. Mean nerve‐to‐vessel signal ratios in 7 subjects were 0.40 ± 0.17 for iMSDE and 0.63 ± 0.37 for OC‐MDSDE. Conclusion OC‐MDSDE combined with 3D TSE in the extremities allows high‐near‐isotropic‐resolution imaging of peripheral nerves with reduced vessel contamination and high nerve signal. Magn Reson Med 79:407–415, 2018. © 2017 Wiley Periodicals, Inc.